2012
DOI: 10.1016/j.jsb.2012.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Integrated control of axonemal dynein AAA+ motors

Abstract: Axonemal dyneins are AAA+ enzymes that convert ATP hydrolysis to mechanical work. This leads to the sliding of doublet microtubules with respect to each other and ultimately the generation of ciliary/flagellar beating. However, in order for useful work to be generated, the action of individual dynein motors must be precisely controlled. In addition, cells modulate the motility of these organelles through a variety of second messenger systems and these signals too must be integrated by the dynein motors to yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 80 publications
(95 reference statements)
0
34
0
Order By: Relevance
“…Only a few cases have been reported where proteins are thought to interact directly with the motor domain of a dynein (53)(54)(55). Based on biochemical evidence, Patel-King and King (55) have reported that the 22-kDa LC1 likely forms a bridge between the ODA γ HC motor domain and the DMT in axonemes, possibly providing limiting doublet sliding in the axonemal bend.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few cases have been reported where proteins are thought to interact directly with the motor domain of a dynein (53)(54)(55). Based on biochemical evidence, Patel-King and King (55) have reported that the 22-kDa LC1 likely forms a bridge between the ODA γ HC motor domain and the DMT in axonemes, possibly providing limiting doublet sliding in the axonemal bend.…”
Section: Discussionmentioning
confidence: 99%
“…The CMF22 IQ motif is of particular interest because it links CMF22 to potential functions in Ca 2ϩ regulation of flagellar motility, which is conserved across diverse phyla and likely has roots in regulatory mechanisms that appeared early in eukaryotic evolution. Chemotaxis of mammalian sperm as well as flagellated protists is dependent upon modulation of the motility apparatus in response to extracellular cues, using Ca 2ϩ as the second messenger (12,(77)(78)(79)(80)(81). Targets of Ca 2ϩ are not well understood, but pioneering studies in Chlamydomonas recently identified three axonemal protein complexes that bind calmodulin and are predicted to function in Ca 2ϩ regulation (82)(83)(84).…”
Section: Discussionmentioning
confidence: 99%
“…While the levels of the inner dynein arm I1 subunits IC138 (Bower et al, 2009) and IC140 (Perrone et al, 1998;Yang and Sale, 1998), microtubule doublet inner junction protein FAP20 , outer dynein arm components LC1 and IC69 (King, 2012), radial spoke protein RSP3 (Yang et al, 2006), and axonemal protein MBO2 (Tam and Lefebvre, 2002) were near wild-type levels, the amount of IC97 ) was significantly reduced in the ift57-1 mutant flagella (Fig. 8).…”
Section: Ift57 Is Required For Establishing Normal Flagellar Waveformsmentioning
confidence: 92%